Improving of the Working Bodyâ€™s Screws Joining Elements Digging-Filling Piles - F. Gasimov, A; R. Barkhalov, R (International Journal of Engineering and Technology, 2018)
Extraction piles are widely used in the construction of industrial and civil buildings in poor, sloping slopes in the construction sector. Two methods are used in the placement of filling piles. First, the shingle-bell method is usually applied on the ground that does not explode. The latter is used primarily in avalanche and flowing grass, as well as in pressure and non-pressure aqueous soils. The parts of the body of the working body are coupled together with the help of couplings. These couplings work for both torsion and twisting. As a result of the gravity force of the large-diameter and deep wells connected to the reducer, the joining element of the couplings is bent. During disassembly, the connecting element is removed and can not be separated from the snap. This problem has once again been confirmed at meetings with producers participating in the BAUMA 2013 exhibition in Munich, Germany. In order to solve this problem it is planned to use the keysing pipe combination.Â Â
Keywords: pile; ground; shaft-wedge; screw; reducer; well; connecting element; keysing pipes.